2021
DOI: 10.1101/2021.03.13.21253492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persisting Salivary IgG against SARS-CoV-2 at 9 Months After Mild COVID-19: A Complementary Approach to Population Surveys

Abstract: Background: Declining humoral immunity in COVID-19 patients and possibility of reinfections has raised concern. Mucosal immunity particularly salivary antibodies could be short-lived. However, long-term studies are sparse. Methods: Using a multiplex bead-based array platform, we investigated antibodies specific to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins in 256 saliva samples from convalescent patients 1-9 months after symptomatic COVID-19 (n=74, Cohort 1), undiagnosed individuals … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Similarly, data from previous cross-sectional studies showed detectable SARS-CoV-2 -specific IgA and IgG levels in saliva 2-4 weeks after onset of symptoms, with only IgG response antibodies persisting beyond 60 days [8,9]. A different study reporting results from single saliva samples collected <3 to 9 months after onset of disease showed a consistently high IgG positivity, but a significant decrease of IgA [10]. In a longitudinal study including 95 participants, the mean time from disease onset to IgG detection in saliva was 9-11 days and IgG antibodies remained detectable until day 90 [19].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similarly, data from previous cross-sectional studies showed detectable SARS-CoV-2 -specific IgA and IgG levels in saliva 2-4 weeks after onset of symptoms, with only IgG response antibodies persisting beyond 60 days [8,9]. A different study reporting results from single saliva samples collected <3 to 9 months after onset of disease showed a consistently high IgG positivity, but a significant decrease of IgA [10]. In a longitudinal study including 95 participants, the mean time from disease onset to IgG detection in saliva was 9-11 days and IgG antibodies remained detectable until day 90 [19].…”
Section: Discussionsupporting
confidence: 56%
“…The sensitivity of both assays was high (IgA: 95.5%; IgG: 89.7%) without compromising specificity (IgA: 99%; IgG: 97%). Other published studies have shown high sensitivity for IgG (88-98.4%), but low (17-59%) for IgA, with a high specificity for both isotypes (96-100%) [8][9][10][11]. Difference in sensitivity between our and other IgA assays could be explained by the assay platform, type of sample, or collection time after infection.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 13 , 21 Newer studies in Sweden show that the antibodies against SARS-COV-2 are detectable 9 months after the infection. 22 The strong immune response after a natural infection with SARS-COV-2 is also supported by the low incidence of breakthrough infections among seropositive compared to seronegative individuals across various age groups. 23 , 24 For example, in large cohort in England (n=2,111), seropositive individuals tested at least monthly were 41-85% less likely to have a positive PCR test for SARS-COV-2 when compared to seronegative individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Antibodies binding to the full-length spike glycoprotein in trimeric form (Spike-f) and the S1 subunit were measured by means of a multiplex bead-based assay in the 384-well plate format (38, 39) as previously described. Briefly, the antigens were immobilized on the surface of uniquely color-coded bead identities (IDs) (MagPlex-C, Luminex corp.), and the IDs pooled to generate the bead-array.…”
Section: Methodsmentioning
confidence: 99%